2010
DOI: 10.1007/s10029-010-0768-7
|View full text |Cite
|
Sign up to set email alerts
|

Not all biologics are equal!

Abstract: The results from this study underscore the difficulty of repairing complex abdominal wall defects in contaminated fields. Cross-linked porcine biologics showed relatively higher infection and explantation rates. Equivalent recurrence and explantation rates were observed for the non-cross-linked porcine biologics and AlloDerm. These data indicate that there is currently no ideal biologic for complex ventral hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 39 publications
2
76
1
1
Order By: Relevance
“…From these eligible articles were found to have partial or complete data available for the population of interest and were used for the synthesis of results (Table 4). [14][15][16][17][18][19][20][21][22][23][24] These articles provided data regarding the following biologic mesh products: AlloDerm (n ¼ 7); Surgisis (n ¼ 2); CollaMend (n ¼ 2); Permacol (n ¼ 2); Strattice (n ¼ 1); and Veritas (n ¼ 1) (see Table 4 footnotes for manufacturers). None provided data on surgical repair procedures conducted using synthetic mesh or no mesh.…”
Section: Study Selection and Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From these eligible articles were found to have partial or complete data available for the population of interest and were used for the synthesis of results (Table 4). [14][15][16][17][18][19][20][21][22][23][24] These articles provided data regarding the following biologic mesh products: AlloDerm (n ¼ 7); Surgisis (n ¼ 2); CollaMend (n ¼ 2); Permacol (n ¼ 2); Strattice (n ¼ 1); and Veritas (n ¼ 1) (see Table 4 footnotes for manufacturers). None provided data on surgical repair procedures conducted using synthetic mesh or no mesh.…”
Section: Study Selection and Synthesis Of Resultsmentioning
confidence: 99%
“…15 Shah et al reported a 25% (1 of 4) rate of recurrence with CollaMend or another porcine cross-linked acellular dermal matrix, Permacol. 24 In the study from Parker et al, 22 it was not possible to determine the rate of hernia recurrence in the target population, although only 1 patient experienced hernia recurrence during an average of 18. 24 which included 5 types of biologic mesh, the lowest infection rates were observed in patients treated with AlloDerm (39.3% versus 75% with cross-linked porcine Permacol/CollaMend and 64.7% with non-cross-linked porcine Surgisis/Strattice).…”
Section: Hernia Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…22 Clinical studies have shown the utility of PADM in several surgical procedures, including chest wall reconstruction, 23 breast reconstruction surgery, 24 and ventral herniorrhaphy. 25 To date, limited data have been reported about biologic matrix use in laparoscopic inguinal herniorrhaphy. [26][27][28] To the author's knowledge, results from studies assessing the use of PADM in laparoscopic inguinal hernia repair have not been previously reported.…”
mentioning
confidence: 99%